Endovascular Perforation Subarachnoid Hemorrhage Fails to Cause Morris Water Maze Deficits in the Mouse. Issue 9 (September 2014) - Milner, Eric; Holtzman, Jacob C; Friess, Stuart; Hartman, Richard E; Brody, David L; Han, Byung H; Zipfel, Gregory J
Cognitive dysfunction is the primary driver of poor long-term outcome in aneurysmal subarachnoid hemorrhage (SAH) survivors; modeling such deficits preclinically is thus key for mechanistic and translational investigation. Although rat SAH causes long-term deficits in learning and memory, it remains unknown whether similar deficits are seen in the mouse, a species particularly amenable to powerful, targeted genetic manipulation. We thus subjected mice to endovascular perforation SAH and assessed long-term cognitive outcome via the Morris water maze (MWM), the most commonly used metric for rodent neurocognition. No significant differences in MWM performance (by either of two protocols) were seen in SAH versus sham mice. Moreover, SAH caused negligible hippocampal CA1 injury. These results undercut the potential of commonly used methods (of SAH induction and assessment of long-term neurocognitive outcome) for use in targeted molecular studies of SAH-induced cognitive deficits in the mouse.